Three Paradoxes of Climate Truth for the Anthropocene Social Scientist. (December 2021) - Jennings, P. Devereaux; Hoffman, Andrew J.
Climate change has been one of the most contested truths for the past two decades. Many social scientists within the academy and this volume have spent years discerning the nature of this truth and articulating its importance for business, organizations, and society. Yet these same scholars face a triple paradox in their work on this important issue. In this essay, we examine those paradoxes—(1) The Paradox of Eliminating the Main Driver, (2) The Paradox of Objectivity and Passion, and (3) The Paradox of Double Irrelevance—and how they are amplified by two institutional factors—the construction of climate truth and its translation in relational fields. We revisit not only how the three paradoxes affect the Anthropocene social scientist as an individual, but, in light of the paradoxes and the two amplifying institutional factors, how she or he might rebalance these tensions by pushing back on each while embracing paradox in personal choices.